Celeribacter litoreus sp. nov., isolated from intertidal sediment. Issue 2 (14th February 2022) - Li, Yi; Ding, Yun-Yun; Dang, Yan-Ru; Bai, Yun; Guan, Li; Liu, Ning-Hua; Wang, Yu-Zhu; Kang, Mei-Lin; Zhang, Yu-Qiang; Zhang, Xi-Ying
Abstract : A Gram-negative, aerobic, non-flagellated and rod-shaped bacterium, strain ASW11-22 T, was isolated from an intertidal sediment collected from a coastal area of Qingdao, PR China. The strain grew at 15–40 °C (optimum, 37 °C), at pH 6.0–9.0 (optimum, pH 7.0) and with 0.5–10 % (w/v) NaCl (optimum, 1.0 %). It hydrolysed gelatin and aesculin but did not reduce nitrate to nitrite. Phylogenetic analysis based on 16S rRNA gene sequences revealed that strain ASW11-22 T belonged to the genus Celeribacter, showing the highest sequence similarity to the type strains of Celeribacter halophilus MCCC 1A06432 T (98.20 %) and Celeribacter ethanolicus NH195 T (97.84 %). The genomic DNA G+C content was 59.1 mol%. The major cellular fatty acid (>10 %) of the strain was summed feature 8 (C18 : 1  ω7 c and/or C18 : 1  ω6 c ) and its main polar lipids were phosphatidylglycerol and one unidentified aminolipid. The sole respiratory quinone of strain ASW11-22 T was ubiquinone-10. On the basis of the polyphasic evidence presented in this paper, strain ASW11-22 T represents a novel Celeribacter species, for which the name Celeribacter litoreus sp. nov. is proposed. The type strain is ASW11-22 T (=KCTC 82495 T =MCCC 1K05584 T ).